Opportunities and challenges in developing potential of Batu Angus as geotourism in Ternate City - Riri Rodiah Noer Syahsiaty; Kadek Wiweka; Rd. Rita Ritasari (Universitas Merdeka Malang, 2026)
Gamalama Mountain erupted in 1907, leaving behind a vast expanse of enough lava rocks area now called Batu Angus Geotourism in Ternate City. With its geological, ecological, and cultural value, this area can become a tourist destination. As national Geopark and has potential to be Global Geopark, this study aims to identify the potential, opportunities, and challenges in the development of Batu Angus as a geo tourism destination in Ternate. This applies a naturalistic qualitative approach, using interviews, observations, and literature review. Therefore, a SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats associated with the development of the area. The results showed that the main strengths are local wisdom, unique geology, and local government support. External opportunities are indicated by the trend of educational tourism, support for academic research, and digital promotion. However, limited infrastructure, a lack of interpretive facilities, and a lack of human resources remain obstacles. This research provides theoretical benefits for the development of literature on geotourism, as well as practical benefits for data-based strategic planning. pentahelix which emphasizes conservation, education, and empowerment. The results of this study also serve as policy recommendations and a basis for developing a roadmap.